Prawne aspekty finansowania systemu ochrony zdrowia we Włoszech - Lenio, Paweł (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
This article raises the subject of legal aspects of financing health protection in Italy. The Italian health system in its existing shape constitutes the effect of reforms carried out over several decades and it has been based on the National Health Service. It is financed from public funds from the state’s budget and regional budgets. The participation of beneficiaries, who are obliged to pay a fee for some types of benefits, in financing healthcare benefits is also significant. In the Italian health care system there is no public health insurance. State administration bodies are responsible for the structure and income efficiency of the sources of financing of the National Health Service in Italy. The sources, however, have been provided for the disposal of Italian regions
Keywords: financing; health protection; Italy